Multiple Access Network Optimization Aspects via Swarm Search Algorithms - Abrão, Taufik; Sampaio, Lucas Hiera Dias; Jr., Mario Lemes Proença; Angélico, Bruno Augusto; Jeszensky, Paul Jean E. (IntechOpen, 2011)
None